Cotton Cost-Return Budget in Central Kansas - Dhuyvetter, Kevin C.; Duncan, Stewart R. (My University, 2001)
This publication projects a budget that reflects expected income and costs based on production of cotton in central Kansas.
MF939_2001_10
Keywords: MF939; Economics; Crops; MF